Characteristics the Structural, Morphological and optical properties of Cd1-xSnxS thin films - J.Ghdeeb, Nadia (مجلة كلية التربية, 2020)
The Cd1-xSnxS thin films were deposited positively on the glass bases by pyrolysis method. Films have grown in the substrat temperature is 300 ° C. The thickness of the films (200±5)nm. XRD files have shown that polycrystalline films the hexagonal structure grew preferentially along the axis (002). The Optical studies carry direct transfer allowed. Energy gap Vary from 2.35 to 2.4 eV.